2003
DOI: 10.1046/j.1365-4362.2003.01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term control of mycosis fungoides of the hands with topical bexarotene

Abstract: Topical bexarotene is effective as long-term treatment monotherapy for limited MF lesions. To our knowledge this is the longest use of the drug by any individual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[18][19][20] Lately, there have been reports that UVA1 irradiation is quite effective on MF in the patch and plaque stages. Plettenberg et al 21 reported that UVA1 therapy for early MF cases in stage IA-IB was more effective and achieved faster response than was PUVA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Lately, there have been reports that UVA1 irradiation is quite effective on MF in the patch and plaque stages. Plettenberg et al 21 reported that UVA1 therapy for early MF cases in stage IA-IB was more effective and achieved faster response than was PUVA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Topical bexarotene is effective as a long-term monotherapy for limited MF lesions, but may be less convenient than other topical therapies as it requires application several times per day [33]. A Phase I/II trial involving 67 Stage IA-IIA MF patients demonstrated a complete response (CR) in 21%, a PR in 42%, and a median time to response of approximately 20 weeks.…”
Section: Efficacymentioning
confidence: 99%
“…New therapeutic approaches are in an experimental phase, as for example immunotoxins (denileukin diftitox, said to be selective against neoplastic T cells), more potent immunomodulating cytokins (recombinant IL-12 to exacerbate innate anti-tumor immune mechanisms), immunotherapy using dendritic cells adhered to tumor antigens, immunization with synthetic peptides or DNA plasmids that express a variable region of Tcell beta receptor and, in the future, genetic and protein transduction to correct intracellular defects of neoplastic T cells. 8,9 Finally, worth of mention is photochemotherapy with PUVA, the object of the present study. The method consists of irradiation of the skin with ultraviolet A rays that is associated with the oral use of psoralen, thus having a phototoxic effect on the skin.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Neoplastic cells of mycosis fungoides correspond to clones of memory T cells that migrate to the superficial dermis and epidermis, which favors the use of skin-oriented therapies. [7][8][9][10][11][12][13][14][15] The treatment of CTCL is still controversial, and various therapeutic methods are proposed to approach it, without an actual consensus on the best treatment to be used. Data from the literature show that successful treatment depends directly on the development phase in which the disease is, besides each patient's individual response.…”
Section: Introductionmentioning
confidence: 99%